Selected aspects of settlement generalization in the General Geographic Database in Poland - Karsznia, Izabela (Geodesy and Cartography, 2013)
The aim of the study was to investigate and highlight the specifics of settlements generalization in the General Geographic Database in Poland. As all the settlements are presented by signatures and selected, bigger ones by outlines – two important aspects were taken into consideration. First of all an attempt of formulating a formal criteria of settlements selection presented by signatures was conducted. The main challenge in this aspect was to achieve a high degree of formalization and automation in the generalization process with inclusion of the specifics of generalized features. In order to fulfil those conditions a concept of regional differentiation of parameters in the settlements selection process was proposed. Additionally the possibilities of contextual settlements’ outlines aggregation and simplification with the application of mathematical morphology operations were also investigated. By applying functions of modified erosion and dilation in the settlements’ outlines aggregation as well as using a simplification algorithm it was possible to achieve results which are cartographically correct in the terms of shape generalization.